Federal Aviation Agency Air Traffic Control Operations : hearings before the United States House Committee on Government Operations, Subcommittee on Government Activities, Eighty-Ninth Congress, second session, on Apr. 26, 27, 1966. (U.S. Congressional Hearings., 1966)
Examines FAA coordination of pilot certification, airport location, and air traffic safety regulations.